Mosaicism of alpha-synuclein gene rearrangements: report of two unrelated cases of early-onset parkinsonism - Perandones, Claudia (2014)
Fil: Perandones, Claudia. ANLIS Dr.C.G.Malbrán. Dirección Científico Técnica; Argentina.